P080 Assessment of environmental exposures in the canadian healthy infant longitudinal development (CHILD) birth cohort. (1st September 2016) - Takaro, Tim K; Scott, James; Allen, Ryan; Becker, Allan; Befus, Dean; Lefebre, Diana; Mandhane, Piush; McLean, Kathleen; Sbhihi, Hind; Brauer, Michael; Shu, Huan; Subbarao, Padmaja; et al.
Abstract : The Canadian Healthy Infant Longitudinal Development (CHILD) birth cohort was designed to elucidate environment-gene relationships underlying the development of asthma and allergy. 3, 624 pregnant mothers were recruited from four provinces in Canada. 3542 infants were eligible for the study and have detailed longitudinal individual-level data. Key domains investigated include indoor and outdoor air pollutants, household chemicals, mould, and other biological allergens, behaviour, infections, gut microbiome, nutrition, psychosocial environment and medications. Assessments of early life exposures focus on inflammatory responses driven by the acquired and innate immune systems. Half of the cohort has reached the 5-year diagnostic endpoints of asthma and allergy. Methods: Exposure assessment methods include extensive environmental questionnaires including time-activity-behaviour at several time points until age five. House dust was collected at 3–4 months, and biological specimens were obtained for multiple exposure-related measurements. Homes and daycares were geo-coded to apply to individual-level land-use regression estimates for traffic-related air pollutants. Results: The data show a geographic variation in the housing age, with the greatest percentage of new homes (built after 1989) in Edmonton (51%) and more families living in older homes (built before 1970) in Winnipeg and Toronto (52% each). Edmonton had the largest number of homes with attached garages (41%) and Vancouver the fewest (13%). Outdoor air pollution estimates are from land-use regression models of nitrogen dioxide (NO2) levels at the home address. Median outdoor NO2 concentration ranges from 4 ppb (Winnipeg) to 13.5 ppb (Toronto). At 3 months of age, 1947/2607 (74.7%) had detectable cotinine in urine while 1575/1583 (99.5%) had detectable phthalate metabolites in urine Discussion: Detailed longitudinal individual-level data exposure assessment can be accomplished in large cohorts. Assessing the associations between health outcomes and multiple exposures across time is challenging. We will discuss several of the modelling efforts we are testing to address these complexities.